Biologi dan statistik demografi kutudaun Rhopalosiphum rufiabdominale (Sasaki) dan Tetraneura nigriabdominalis (Sasaki) (Hemiptera: Aphididae) di akar padi - Purnama Hidayat; Harleni Harleni; Yani Maharani; Hermanu Triwidodo (Perhimpunan Entomologi Indonesia, 2019)
Rhopalosiphum rufiabdominale (Sasaki) and Tetraneura nigriabdominalis (Sasaki) are aphid species found in the roots of rice plants. Information about the host range and biology of R. rufiabdominale is relatively known than T. nigriabdominalis. This study aims to determine the biology and demographic statistics of R. rufiabdominale and T. nigriabdominalis in the roots of rice plants. The aphids obtained from lowland rice roots in Leuwiliang, Bogor Regency were maintained and reared in Ciherang variety rice roots in the laboratory. Each individual of the 1st instar aphid nymph in the same cohort was infested into the roots of rice in 60 plastic containers for biological observations and statistical demographic variable data collection. Survivorship (lx), fecundity (mx), and the average number of nymphs born by adult every day at age (x) are used to calculate demographic statistical parameters. The results showed that the two species of the aphids have 4 nymph instars. Life cycle and longevity of R. rufiabdominale were 4.98 days and 15.94 days with fecundity of 67.44 respectively, whereas the life cycle and longevity of T. nigriabdominalis were 5.25 days and 18.11 days with fecundity of 11.11 respectively. R. rufiabdominale aphids have an intrinsic growth rate (r) of 0.46 days and a doubling time (DT) of 1.50 days, whereas T. nigriabdominalis has an intrinsic growth rate of 0.14 days and a doubling time of 4.99 days. The results of this study indicate that although the life cycle lengths of the two species are almost the same, the population of R. rufiabdominale develops 3.5 times faster than T. nigriabdominalis and therefore R. rufiabdominale has the potential to become an more important pest in rice plants.